Blastic plasmacytoid dendritic cell neoplasm: a Swiss case series of a very rare disease and a structured review of the literature - Ramona Meier-Lienhard; Cosima Suter; Thomas Pabst; Felicitas Hitz; Jakob R. Passweg; Olivier Spertini; Nathan Cantoni; Daniel Betticher; Lucas Simeon; Michael Medinger; Stefanie Hayoz; Adrian Schmidt (Swiss Medical Weekly)
INTRODUCTION: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a very rare disease, with unique diagnostic challenges and often dismal outcome. There are no widely accepted treatment guidelines available. Lymphoma-like regimens with or without autologous or allogenic transplantation were the cornerstone of most therapeutic concepts. A few years ago, the CD123-directed immunoconjugate tagraxofusp emerged as a new valuable treatment option. The goal of our research was to collect available data on BPDCN-patients treated at large centres in Switzerland and worldwide and to draw conclusions regarding the incidence, clinical presentation, prognostic factors and therapeutic strategies.